Dampak Aktivitas Operasional Terhadap Penerimaan Sisa Hasil Usaha Koperasi Bmt Tarbiyah Palembang - Muhammad Fauzan Anhaf; Sukmini Hartati (Politeknik Negeri Sriwijaya, 2020)
This research to analysis of Effect of Credit Sales and Operating Expenses Against Acceptance Time Results of Operations (SHU) Cooperative BMT Tarbiyah Palembang. The research data sourced from financial statements cooperative BMT Tarbiyah Palembang. Model analysis used simple linear regression where the variables used in this study consisted of free variable, namely: credit sales (XI), operating expenses (X2), and the dependent variable is the balance of the (Y). In accordance with the results of statistical analysis, it turns out jointly and variable partial credit sales and operating expenses had a significant effect on the balance of the (SHU) at BMT cooperative Tarbiyah Palembang.